Soul and Body Sane Quality Improvement: Senior High School Students' Reveal Surprising Experiences in P5 Activities - Prasiwi, Jesita; Raihan, Raden Muhammad; Ratnasari, Dwi; Fitriyanti, Eka (Jurnal Pendidikan Abad Ke-21, 2024)
Students feel that P5 activities are exciting and fun because they are instructed to memorize gymnastic movements and musical drama dialogues, and they can enjoy the activities that are carried out. Students get perceived benefits from gymnastics and musical drama exercises. Obstacles or difficulties during P5 activities are difficulties finding the property, generally in finding a place with a relatively low price. Skills homed in P5 activities include skills to train cohesiveness in teamwork because activities focus on collaborative activities. P5 activities are carried out with an allocation of time for two consecutive weeks without involving other academic activities. This schedule selection makes students feel unburdened or pressured to work on the P5 final project and can complete it with focus.